2023
DOI: 10.3390/ma16062219
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Standard Deviation of Cationic Radii on the Transition Temperature in Fluorite-Structured Entropy-Stabilized Oxides (F-ESO)

Abstract: It is confirmed that Fluorite-structured Entropy-Stabilized Oxides (F-ESO) can be obtained with multicomponent (5) equimolar systems based on cerium, zirconium, and other rare earth elements, selected according to the predictor already proposed by the authors. Indeed, in the present study, three different samples owning a standard deviation (SD in the following) of their cationic radii greater than the threshold value (i.e., SD > 0.095 with cationic radii measured in Å) needed to ensure the formation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…The formation of single-phase HEFOs has been widely investigated, with theoretical advancements also aiding in the prediction of such phase formations. Spiridigliozzi et al [26] introduced the standard deviation of atomic radii as an indicator for predicting the formation of single-phase HEFOs, positing that greater variance among atomic radii increases the likelihood of the formation of fluorite-structured HEFO. Focused research on the synthesis and application of these oxides has indicated intriguing structural symmetry transition behaviors [25,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of single-phase HEFOs has been widely investigated, with theoretical advancements also aiding in the prediction of such phase formations. Spiridigliozzi et al [26] introduced the standard deviation of atomic radii as an indicator for predicting the formation of single-phase HEFOs, positing that greater variance among atomic radii increases the likelihood of the formation of fluorite-structured HEFO. Focused research on the synthesis and application of these oxides has indicated intriguing structural symmetry transition behaviors [25,28].…”
mentioning
confidence: 99%
“…In this study, we selected representative HEFO, composed of the commonly used fluorite bases CeO 2 , HfO 2 , and ZrO 2 , along with rare earth oxides such as Gd 2 O 3 and La 2 O 3. This composition results in a significant standard deviation in cationic radii of 0.1624 Å, indicative of high propensity for the formation of a single-phase fluorite structure [26]. We designated this synthesized material as (CeHfZrGdLa)O x (Ce-HEO) and subjected it to prolonged annealing at its intended operational temperature to demonstrate high-temperature stability behavior of HEFO.…”
mentioning
confidence: 99%